PERSOALAN LINGKUNGAN DAN PEMBERDAYAAN MASYARAKAT LOKAL: LESSONS LEARNED DARI INDONESIA BAGIAN TIMUR - Yulianto, Sg. (Universitas Mahasaarswati Denpasar, 2012)
Nowadays, the issues of environment are increasingly disturbing. By regulations and the schemes of program, the governments (national and local) have made efforts to overcome the problems. The results however have yet met the public expectations. Amidts the increased pesimism of the public over the efforts, there have been several success stories of grassroots that can please and encourage the public optimism on the improvement and preservation of the natural environment.The efforts of local communities empowerment, through the program scheme launched by some local civil society organizations, have successfully made the communities to be aware of the enviromental crisis, and encouraged them to protect their environment from any destruction, perpetrated by both corporates and their fellow villagers. Such efforts also become the alternative breakthroughs to overcome their economic problems as well as promoting the protection and conservation of the environment, which can also make sure the sustainability of their livelihoods.